A Tafsir Maudhu’i Perspective on Business, Trade, and Economy in the Qur'an - Zainal Abidin (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
Islam as a universal, integral, and comprehensive living system has established a complete order for human life. As a way of life, Islam organized all the things that related to life, from the simplest thing to the most complicated matters even though. Both in political, economic, education, art, social, cultural, etc. Islam is the perfect religion, which regulates things related to the economy. If the economy of a country (the national economy) applies the basics of the Qur'an and Hadith as well as the basis of the application, of course, a national economy will run well and purposeful according to the rules. However, the reality is that not all Muslim countries in the world are implementing the foundation. Furthermore, in this article it is explained about how the Islamic Economy contributing to the development of the national economy, especially Indonesia as a country by the largest Muslim base is se-Asian.